THE MANHAJ TARBIYAH RĀBIʻAH AL- ʻADAWĪYAH APPROACH USED IN OVERCOMING DEPRESSION - Izzati Ahmad, Nur; Z., Ab Rahman (International Journal of Psychosocial Rehabilitation, 2022)
Newspapers had lately highlighted the increasing number of mental health problem cases, especially depression. Thus, several studies intended to examine the use of spiritual methods to overcome the problem of depression. However, no study has yet to investigate the use of the Manhaj Tarbiyah approach by -, a Sufi figure, to investigate depression. This study aims to scientifically examine the Manhaj Tarbiyah RĀBIʻAH AL- ʻADAWĪYAH - approach applied when dealing with the problem of depression. This qualitative study used the content analysis method to analyze documents, such as newspaper reports, manuscripts, journals and review articles related to the use of the - teaching method when dealing with depression. The contents were analyzed to identify the elements in the - RĀBIʻAH AL- ʻADAWĪYAH Manhaj Tarbiyah approach. A literature review found that this approach, which was in the form of poetry, was successful in overcoming depression.